﻿INFLUÊNCIA DO PROCESSAMENTO NA OBTENÇÃO DE BIOCERÂMICAS À BASE DE HIDROXIAPATITA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
Calcium phosphate ceramics have been intensely investigated as bone implant material, amongst them hydroxyapatite (HAP) outstands, which has been widely used in medicine and dentistry for presenting excellent biocompatibility. Due to its chemical similarity to the bone mineral phase, it establishes chemical liaisons with the host tissue, helps in the bone growth and allows cell proliferation. However, its use is limited for presenting poor mechanical resistance. Alternatives to overcome such limitations consist of changing the synthesis route or the composite material preparation. Recently, the hydroxyapatite synthesis in the presence of collagen has been explored, however due to problems related to cost, availability and commercial origin; the collagen was substituted by commercial gelatin in this experiment. Four processing routes, involving the precipitation method were evaluated: hydroxyapatite, with, and without gelatin, powder drying process in oven and through liofilization. X-ray fluorescence results indicate that the Ca/P molar ratio of obtained materials is lower than 1,67; IR analyses suggest the formation of calcium deficient carbonated apatite from the samples without thermal treatment and for the ones thermally treated up to 700ºC. DRX analysis confirms the biphasic ceramic formation, in the presence of β-TCP as a secondary phase, after sintering at 1200ºC. The ratio between TCP/HAP phases of samples thermally treated at 1200ºC increased with the decrease of precursor powder Ca/P molar ratio. Results of diffractograms refinement through the Rietveld Method indicated that samples synthesized in the presence of gelatin presented the lowest β-TCP percentage after sintering at 1200ºC. Particle size distribution analysis indicated that the gelatin presence led to formation of clusters of smaller average diameter. It is believed that its presence be related to changes in the nucleation process and grain growth. For mechanical evaluation, samples were prepared through uniaxial pressing followed by cold isostatic with 200MPa compaction pressure and sintered at 1200ºC for two hours in oxidant atmosphere. It was observed that the presence of gelatin enhanced densification and resulted in higher hardness for the compacts. The facture surface microstructure revealed lower porosity for samples synthesized in the presence of gelatin compared to conventional samples and for the liofilized samples compared to the ones dried in oven. Regarding resistance to bending, values obtained are comparable to the cortical bone, being the highest value obtained from the conventional liofilized hydroxyapatite sample.
Keywords: biomaterial; hidroxiapatita; gelatina; propriedades mecânicas.; biomaterial; hydroxyapatite; gelatin; mechanical properties.; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA